Serum sCD95L concentration in patients with spinal cord injury - Biglari, Bahram; Büchler, Axel; Swing, Tyler; Child, Christopher; Bruckner, Thomas; Ferbert, Thomas; Korff, Sebastian; Rief, Harald; Gerner, Hans-Jürgen; Moghaddam-Alvandi, Arash (The journal of international medical research, 2015)
ObjectiveTo determine serum concentrations of soluble CD95 ligand (sCD95L) in patients with traumatic spinal cord injury.MethodsPatients with traumatic spinal cord injury were recruited. Blood was collected on admission to hospital and at 4?h, 9?h, 12?h, 24?h, 3 days, 7 days, and 2, 4, 8 and 12 weeks postadmission. Serum concentrations of sCD95L were determined via immunoassay.ResultThe study included 23 patients. Mean sCD95L concentrations were significantly lower at 4?h, 9?h, 12?h and 24?h than at admission, and were significantly higher at 8 and 12 weeks, compared with admission.ConclusionThe serum sCD95L concentration fell significantly during the first 24?h after traumatic spinal cord injury. Concentrations then rose, becoming significantly higher than admission levels at 8 weeks. sCD95L may represent a possible therapeutic target for traumatic spinal cord injury.